PENGARUH ROLE STESSOR, SELF-EFFICACY, SENSITIVITAS ETIKA PROFESI DAN KOMITMEN ORGANISASI TERHADAP KINERJA AUDITOR DENGAN EMOTIONAL QUOTIENT SEBAGAI VARIABEL MODERATING (Studi Empiris pada Auditor Kantor Akuntan Publik di Padang, Pekanbaru dan Batam) - Arfiah Ismail Arfiah Ismail; Yuneita Anisma Anisma; Rofika Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
his research aimed to determine the effect of role stressor, selfefficacy,sensitivityprofessional ethicand organization commitment toauditors performance with the emotional quotient as moderating variable to public accountant office in Padang, Pekanbaru and Batam. This study useda primary data was collected by questionnaire distribution to auditors. Sample was determined by purposive sampling amounted to 60 auditors. Data was collected by using a purposive sampling.After the data was collected, the data was analyzed by using the SPSS program to test whether the model used in this study quite appropriate as the model analyzed. Then the regression analysis was used to test the relationship between the variables above. On the model one, the result of this research indicate that role conflict, role ambiguity, self-efficacy, sensitivity professional ethic and organization commitment had a positive effect and significant on auditors performance. On the model two, the moderating of emotional quotientto had a positive effect and significant between role conflict, self-efficacy, sensitivity professional ethic, organization commitment on auditors performance. But, the moderating of emotional quotient had a negative effect and not significant between role ambiguity on performance auditors.Keywords: Role Conflict, Role Ambiguity, Self-Efficacy, Sensitivity Professional Ethic, Organization Commitment, Performance Auditors, Emotional Quotient.